2018
DOI: 10.1155/2018/9480497
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Seen by Our Cells: The Role of Viral RNA Sensors

Abstract: The role of the innate immune response in detecting RNA viruses is crucial for the establishment of proper inflammatory and antiviral responses. Different receptors, known as pattern recognition receptors (PRRs), are present in the cytoplasm, endosomes, and on the cellular surface. These receptors have the capacity to sense the presence of viral nucleic acids as pathogen-associated molecular patterns (PAMPs). This recognition leads to the induction of type 1 interferons (IFNs) as well as inflammatory cytokines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 154 publications
(161 reference statements)
0
74
0
Order By: Relevance
“…Different early stages of HIV-1 infection, such as virus attachment and accumulation of reverse-transcription products in cells, can induce multiple signaling events, which can lead to many changes in cellular functions (33,34). Using NVP treatment of HIV-1-infected cells and heat-inactivated HIV-1 as controls, we demonstrated that viral replication is not required for the up-regulation of m 6 A levels of cellular RNA.…”
Section: Discussionmentioning
confidence: 90%
“…Different early stages of HIV-1 infection, such as virus attachment and accumulation of reverse-transcription products in cells, can induce multiple signaling events, which can lead to many changes in cellular functions (33,34). Using NVP treatment of HIV-1-infected cells and heat-inactivated HIV-1 as controls, we demonstrated that viral replication is not required for the up-regulation of m 6 A levels of cellular RNA.…”
Section: Discussionmentioning
confidence: 90%
“…To facilitate comparison between the respiratory viruses described here, known and arguably important innate immune evasion strategies are listed, and for each strategy it is discussed how each virus group exploits its own mechanism. Innate immune evasion obviously links to the innate immune responses that are known to be elicited by respiratory and other (RNA) viruses, and while this will be elaborated to a limited extent below, they have also been reviewed comprehensively in recent reviews by others [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…PAMPs consisting of viral RNA, DNA and proteins are recognized by pattern recognition receptors (PRRs) expressed and sensed by DCs. PRRs include Toll-like receptors, RIG-like receptors, NOD-like receptors and cGAS [ 81 , 82 , 83 ]. Due to the involvement of PRR, DC produces pro-inflammatory cytokines (e.g., TNF-α and IL-12) and antiviral type I IFN.…”
Section: The Tme and Ov Infectionmentioning
confidence: 99%